ex 2 si 3
dau coroana.............
Anexe:
Răspunsuri la întrebare
Răspuns de
3
Răspuns:
2. f:R -> R, f(x)= (m²-2)x-3 - str. descrescatoare <=> m²-2<0
m²-2=0 <=> (m+2)(m-2)=0 => m=±2
m: -∞ -2 2 +∞
m²-2: -∞ +++++ 0 - 0 ++++
m²-2<0 => m∈ (-2,2)
3. arctg (x/3) + arctg( 1/√3) = π/3
<=> tg ( arctg(x/3) + arctg(√3/3) ) = tg (π/3)
<=> tg(arctg (x/3)) + tg( arctg(√3/3)) / 1- tg(arctg (x/3)) * tg( arctg(√3/3)) = √3
<=> x/3 + √3/3 / 1- (x/3)*(√3/3) = √3
<=> x+√3/ 3*(1- x√3/9)=√3
<=> x+√3 / 3* (9-x√3)/3 = √3
<=> x+√3 / 9-x√3 =√3
<=> x+√3 = √3* (9-x√3)
<=> x+√3= 9√3 - 3x
<=> 4x= 8√3
<=> x= 2√3
Răspuns de
0
3)
2)
Anexe:
Alte întrebări interesante
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Religie,
9 ani în urmă
Matematică,
9 ani în urmă